Efficacy and Safety of Transdermal Buprenorphine versus Oral Tramadol/Acetaminophen in Patients with Persistent Postoperative Pain after Spinal Surgery - Jae Hyup Lee; Jin-Hyok Kim; Jin-Hwan Kim; Hak-Sun Kim; Woo-Kie Min; Ye-Soo Park; Kyu-Yeol Lee; Jung-Hee Lee (Pain Research and Management)
Purpose. Control of persistent pain following spinal surgery is an unmet clinical need. This study compared the efficacy and safety of buprenorphine transdermal system (BTDS) to oral tramadol/acetaminophen (TA) in Korean patients with persistent, moderate pain following spinal surgery. Methods. Open-label, interventional, randomized multicenter study. Adults with persistent postoperative pain (Numeric Rating Scale [NRS] ≥ 4 at 14–90 days postsurgery) were enrolled. Patients received once-weekly BTDS (n=47; 5 μg/h titrated to 20 μg/h) or twice-daily TA (n=40; tramadol 37.5 mg/acetaminophen 325 mg, one tablet titrated to 4 tablets) for 6 weeks. The study compared pain reduction with BTDS versus TA at week 6. Quality of life (QoL), treatment satisfaction, medication compliance, and adverse events (AEs) were assessed. Findings. At week 6, both groups reported significant pain reduction (mean NRS change: BTDS −2.02; TA −2.76, both P<0.0001) and improved QoL (mean EQ-5D index change: BTDS 0.10; TA 0.19, both P<0.05). The BTDS group achieved better medication compliance (97.8% versus 91.0%). Incidence of AEs (26.1% versus 20.0%) and adverse drug reactions (20.3% versus 16.9%) were comparable between groups. Implications. For patients with persistent pain following spinal surgery, BTDS is an alternative to TA for reducing pain and supports medication compliance. This trial is registered with Clinicaltrials.gov: NCT01983111.